Polysomnographic recording of nocturnal bruxism before and after placement of an anterior deprogrammer. Registro polisomnográfico del bruxismo nocturno pre y post colocación de un desprogramador oclusal anterior - Martínez Quintero, David; Mosquera Ibarguen, Walter; Urbano Montoya, Lady Johanna; Restrepo Mejía, Francia; López Soto, Olga Patricia; Aristizabal Hoyos, Juan Alberto (CES Odontología, 2013)
Introduction and objective:Bruxism is an oral habit consisting of involuntary and spasmodic clenching of teeth . The anteriordeprogrammer is one of the initial treatments for bruxism and polysomnography is a test that measuresthe number of bruxism events during sleep. To compare the changes occurring in the polysomnographicrecording of nocturnal bruxism after placing the patient on the anterior deprogrammer.Materials and Methods:This descriptive study considered a convenience sample of 10 patients with bruxism. Patients received astreatment an upper anterior deprogrammer for 15 days. Two polysomnographies were done (before andafter placement of the anterior deprogrammer) positioning electrodes to record the electrocardiogram,electroencephalogram, snoring, bruxism and eye movements. For the encephalogram, two electrodeswere connected in the following regions: lateral-anterior, middle, occipital, atrial skull with a centralelectrode and ground poles . Records were taken during eight hours of nocturnal sleep.Results:n phase 1, it was found Conclusion:The anterior deprogrammer decreased the number of bruxism events during sleep in the cases consideredin this study according to polysomnographic recordings.Key words:Bruxism, Polysomnography, Dental Occlusion.the average number of bruxism events was reduced 53.1%; in phase 2 in41.9%; in phase 3 in 37.8% and in REM sleep, there was a decrease of 23.8%. Averages in phase 2 werestatistically significant. Introducción y objetivo:El bruxismo es el hábito oral de apretamiento de los dientes de manera rítmica y espasmódica. Eldesprogramador oclusal anterior es uno de los tratamientos iniciales del bruxismo y la polisomnografíaes un examen que determina el número de eventos de bruxismo en la noche. Comparar los cambiosque se producen en el registro polisomnográfico del bruxismo nocturno después de la colocación de undesprogramador anterior.Materiales y método:Este estudio descriptivo comparativo consideró una muestra por conveniencia de 10 pacientes conbruxismo. Los pacientes recibieron como tratamiento un desprogramador oclusal anterior superiordurante 15 días. Se realizaron dos polisomnografías (antes y después de la colocación del desprogramadoranterior) posicionando los electrodos para registrar el electrocardiograma, el electroencefalograma, elronquido, el bruxismo y los movimientos oculares .En la conexión del encefalograma, se usaron electrodosen par en las regiones: lateral-anterior, media, occipital, auricular del cráneo, electrodos centrales, ypolos a tierra. Los registros se tomaron durante 8 horas de sueño nocturno.Resultados:En la fase 1, se pudo observar que el número promedio de eventos de bruxismo se redujo en un 53.1%;en la fase 2 en un 41,9%, en la fase 3 en un 37,8% y en la fase REM, hubo una disminución del 23,8%. Lasmedias en la fase 2 presentaron diferencias estadísticamente significativas.Conclusión:El desprogramador anterior disminuyó el número de episodios de bruxismo durante las fases del sueñoen los casos considerados en este estudio.Palabras Clave:Bruxismo, Polisomnografía, Oclusión dental.